1987
DOI: 10.1084/jem.165.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Use of insertional inactivation to facilitate studies of biological properties of pneumococcal surface protein A (PspA).

Abstract: PspA is a cell surface protein of Streptococcus pneumoniae that is present on a number of clinical isolates as well as the nonencapsulated laboratory strain Rx1. In a previous report we have shown that mAbs directed against PspA can protect mice from at least some of the pneumococcal strains bearing this protein. In our present report we have produced insertional inactivation mutants that lack PspA and have used these mutants to demonstrate that PspA can play a role in pneumococcal virulence and that anti-PspA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
152
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 36 publications
4
152
1
1
Order By: Relevance
“…A pspA-deficient derivative of D39, LM91, was provided by Larry McDaniel, University of Alabama, Birmingham, AL, USA. This strain is a null mutant in pspA created by insertion duplication mutagenesis (McDaniel et al, 1987). S. pneumoniae was routinely plated on tryptic soy agar supplemented with sheep blood (3%, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…A pspA-deficient derivative of D39, LM91, was provided by Larry McDaniel, University of Alabama, Birmingham, AL, USA. This strain is a null mutant in pspA created by insertion duplication mutagenesis (McDaniel et al, 1987). S. pneumoniae was routinely plated on tryptic soy agar supplemented with sheep blood (3%, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, in a murine model of bacteremia, PspA-deficient (PspA Ϫ ) pneumococci have significantly reduced virulence compared with pneumococci that express PspA (PspA ؉ ) (2,3). Earlier studies from our laboratory and others' have shown that PspA inhibits complement activation, thereby limiting opsonization of pathogens by complement protein 3 (C3) (4 -7).…”
mentioning
confidence: 99%
“…Pneumococcal surface protein A (PspA) 3 is an important virulence factor for S. pneumoniae (1)(2)(3). Accordingly, in a murine model of bacteremia, PspA-deficient (PspA Ϫ ) pneumococci have significantly reduced virulence compared with pneumococci that express PspA (PspA ؉ ) (2,3).…”
mentioning
confidence: 99%
“…Because it thus can induce cross-reactive immune responses among different strains, PspA is a promising candidate antigen for the development of a next-generation pneumococcal vaccine. 22 , 23 Nasal administration of a fusion protein comprising PspA and flagellin from Vibrio vulnificus induced antigen-specific IgG and IgA both in serum and at mucosal surfaces and provided efficient protective immunity in mice against lethal challenge with live S. pneumoniae . 24 In addition, co-administration of PspA antigen and IL-12 as a nasal adjuvant enhanced PspA-specific IgG and IgA responses, with increased protection from nasal carriage.…”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%
“…28 , 29 These results support PspA as a promising antigen candidate for an S. pneumoniae vaccine that is likely to be effective not only in adults but also in children and the elderly. 30 , 31 …”
Section: Development Of a Nanogel-based Nasal Vaccine Against Pneumoniamentioning
confidence: 99%